2014
DOI: 10.1007/s11099-014-0044-7
|View full text |Cite
|
Sign up to set email alerts
|

Sodium bisulfite enhances photosynthesis in rice by inducing Rubisco activase gene expression

Abstract: To investigate how bisulfite promotes photosynthesis, a pot experiment was conducted with rice (Oryza sativa L.) plants to determine Rubisco activity and content, and Rubisco activase (RCA) gene expression after spraying NaHSO 3 on rice leaves. The NaHSO 3 treatment promoted significantly net photosynthetic rate (P N ), carboxylation efficiency, maximum carboxylation rate, ribulose-1,5-bisphosphate regeneration rate, initial Rubisco activity, and RCA protein and mRNA concentrations. Therefore, the NaHSO 3 enha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 19 publications
1
7
0
Order By: Relevance
“…The activation of Rubisco by RCA serves an important regulatory function in linking the rate of CO 2 fixation to the rate of electron transport activity via the production of ATP (Dias et al 2010, Parry et al 2013. Rubisco catalyzes the first step in the net photosynthetic CO 2 assimilation (Chen et al 2014b), and its activation state is regulated by RCA (Boex-Fontvieille et al 2014). In this study, water loss caused de-activation of Rubisco and RCA, which in turn caused a metabolic limitation to photosynthesis, resulting in a drop of net formation of carbohydrates, such as dry mass.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The activation of Rubisco by RCA serves an important regulatory function in linking the rate of CO 2 fixation to the rate of electron transport activity via the production of ATP (Dias et al 2010, Parry et al 2013. Rubisco catalyzes the first step in the net photosynthetic CO 2 assimilation (Chen et al 2014b), and its activation state is regulated by RCA (Boex-Fontvieille et al 2014). In this study, water loss caused de-activation of Rubisco and RCA, which in turn caused a metabolic limitation to photosynthesis, resulting in a drop of net formation of carbohydrates, such as dry mass.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, Rbc S showed some upregulation, but Rbc L was significantly up-regulated by SA, suggesting that SA could enhance Rubisco biosynthesis under WD. Two RCA genes, ZmRCAα and ZmRCAβ, encoding larger and smaller polypeptides of approximately 46 and 43 kD were found in maize (Yin et al 2014), which ensure a stable RCA structure and maintain initial Rubisco activity under stress conditions (Wang et al 2010, Chen et al 2014b). Different RCA subunits may play different roles in photosynthetic acclimation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ATPase family, which utilizes ATP hydrolysis to remove tight-binding inhibitors and activate the catalytic activity of Rubisco (Henderson et al 2013). It was reported that photosynthesis in rice can be improved by inducing RCA gene expression (Chen et al 2014). Hence, the increased RCA may regulate the initial Rubisco activity, which will be beneficial to carbon fixation.…”
Section: Proteins Related To Superior Photosynthetic Characteristics mentioning
confidence: 99%
“…HSO 3 -could block photorespiration process by forming α-hydroxylsulphonates with glyoxylate to inhibit GO activity (Zelitch 1957). Numerous researches indicated that the application of NaHSO 3 to plants was shown to increase P N in many species (Wang et al 2003, Guo et al 2006, Yang et al 2008, Chen et al 2014, Liu et al 2015. In this experiment, all NaHSO 3 treatments depressed P R .…”
Section: Discussionmentioning
confidence: 63%